THE INFLUENCE ANALYSIS OF LEADERSHIP STYLE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE INTENTION TO STAY MEDIATED BY JOB SATISFACTION IN PRIMARY AND SECONDARY EDUCATION ORGANIZATIONS IN JABOTABEK - Susanti, Yenny; Widhianto, Chandra Wibowo (Ridwan Institute, 2024)
This study aims to analyze the relationship between leadership style (LS), organizational commitment (OC), and employee intention to stay working (ITS) in private primary and secondary education organizations in the form of SPK (Cooperation Education Unit) in Jabotabek, Indonesia, using the PLS-SEM method. The results show that 67.4% of job satisfaction variables can be influenced by leadership style and organizational commitment variables. Organizational commitment and job satisfaction have a positive and significant effect on ITS as an intervening variable. Job satisfaction is able to increase the influence / mediate of leadership style on intention to remain in educational organizations. The managerial advice from this study emphasizes the importance of management in optimizing leadership styles, organizational commitment, and JS to increase employee intention, which has an impact on organizational stability.